Freedom of contract and financial stability through the lens of the Legal Theory of Finance (LTF): LTF approaches to ABS, Pari Passu-Clauses, CCPs, and Basel III - Brigitte Haar (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper is the outcome of a related broader project, exploring the explanatory power of the Legal Theory of Finance, which proposes a new institution-based analytical framework for the analysis of phenomena of financial markets. One of its most important theoretical assumptions, the legal construction of financial markets, is highlighted by the example of the private creation of money by structured finance products in this paper. Further implications can then be shown referring to pari passu clauses and collective action clauses, which are both exhibit a differential application of these legal rules according to the hierarchical status of the respective market participant, and can therefore endanger sovereign debt restructurings. Legal instruments to avoid this are briefly explored. An example of another key role of the law in crisis that is the task to resolve the tension between market discipline and financial stability is exemplified by the regulation of the OTC derivatives market and proposals of effective loss-sharing among CCPs. Related questions about the significance of legal rules to ensure financial stability are raised in the analysis of minimum capital requirements under Basel III.
urn:nbn:de:hebis:30:3-416936
Keywords: G38; K12; K20; K22; N20; O16; 330; law and finance; financial stability; financial contracts; structured finance; asset-backed securities; pari passu clauses; collective action clauses; otc derivatives markets; central counter parties; Basel III; coco bonds